A new species of eriophyoid mite (Acari: Trombidiformes: Eriophyoidea) on Chaenomeles x superba (Frahm) Rehder (Rosaceae) - Soika, Grażyna; Wozińska, Anna (Zootaxa, 2016)
A new species, Epitrimerus chaenomeli n. sp., is described and illustrated in this paper. The description is based on the morphology of protogynes, deutogynes and nymphs. This new species was recorded on Chaenomeles x superba (Frahm) Rehder and its cultivar Crimson and Gold (Rosaceae) which have not previously been noted as a host for eriophyoid mites. Mites of this species caused slight rusting on the under-surfaces of infested leaf blades. In addition, a list of all known species of Epitrimerus found on Rosaceae is also provided.